Lack of Cdkl5 Disrupts the Organization of Excitatory and Inhibitory Synapses and Parvalbumin Interneurons in the Primary Visual Cortex - Pizzo, Riccardo; Gurgone, Antonia; Castroflorio, Enrico; Amendola, Elena; Gross, Cornelius; Sassoè-Pognetto, Marco; Giustetto, Maurizio (Frontiers in Cellular Neuroscience, 2016)
CDKL5 (cyclin-dependent kinase-like 5) mutations are found in severe neurodevelopmental disorders, including the Hanefeld variant of Rett syndrome (CDKL5 disorder). CDKL5 loss-of-function murine models recapitulate pathological signs of the human disease, such as visual attention deficits and reduced visual acuity. Here we investigated the cellular and synaptic substrates of visual defects by studying the organization of the primary visual cortex (V1) of Cdkl5-/y mice. We found a severe reduction of c-fos expression in V1 of Cdkl5-/y mutants, suggesting circuit hypoactivity. Glutamatergic presynaptic structures were increased, but postsynaptic PSD-95 and Homer were significantly downregulated in CDKL5 mutants. Interneurons expressing parvalbumin, but not other types of interneuron, had a higher density in mutant V1, and were hyperconnected with pyramidal neurons. Finally, the developmental trajectory of pavalbumin-containing cells was also affected in Cdkl5-/y mice, as revealed by fainter appearance perineuronal nets at the closure of the critical period. The present data reveal an overall disruption of V1 cellular and synaptic organization that may cause a shift in the excitation/inhibition balance likely to underlie the visual deficits characteristic of CDKL5 disorder. Moreover, ablation of CDKL5 is likely to tamper with the mechanisms underlying experience-dependent refinement of cortical circuits during the critical period of development.